A Trace Formula for Integro-differential Operators on the Finite Interval - Wang, Yu-ping; Koyunbakan, Hikmet; Yang, Chuan-fu (Springer Heidelberg, 2017)
In this paper, we consider the eigenvalue problem for integro-differential operators with separated boundary conditions on the finite interval and find a trace formula for the integro-differential operator.
Keywords: trace formula; integro-differential operator; eigenvalue